Evidence for atmospheric pollution across the Permian-Triassic transition - Hochuli, Peter A; Schneebeli-Hermann, Elke; Mangerud, Gunn; Bucher, Hugo (Geological Society of America, 2017)
Evidence for a cause-and-effect relationship between the emplacement of the Siberian Traps large igneous province and the Permian-Triassic marine mass extinction has been growing over the past decades. However, how the Siberian Traps volcanism affected the terrestrial vegetation is still a matter of controversy. Here, we demonstrate that a substantial part of plants’ life cycle, namely their reproductive organs, was adversely affected by environmental conditions. Effects include malformed spores and pollen grains, unseparated tetrads, and darkened walls of spores and pollen (sporoderm) from Permian-Triassic sediments from the Finnmark Platform offshore Norway. The co-occurrence of these morphological changes with the main carbon isotope excursion and the marine mass extinction may suggest that they were caused by atmospheric pollution linked to Siberian Traps emissions.